2022
DOI: 10.1515/hmbci-2022-0024
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-1α and ischemia-modified albumin levels in intensive care COVID-19 Patients

Abstract: Objectives In this study, it was aimed to evaluate the hypoxia-inducible factor-1α (HIF-1α) and ischemia-modified albumin (IMA) levels of patients diagnosed with COVID-19 in the intensive care unit (ICU) and healthy controls. To our knowledge, this is the first study investigate HIF-1α and IMA levels in COVID-19 patients in ICUs and comparing them with a healthy control group. For this reason, our study is original and will contribute to the literature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In recent studies, higher IMA levels were found in COVID-19 patients compared to control groups [ 24 , 25 , 26 ]. In Yucel et al’s study with 70 patients in the ICU, the serum IMA levels were determined to be significantly higher compared to the healthy control group [ 27 ]. However, in the study of Altıntas et al, no significant difference was determined in the serum IMA levels between the COVID-19 and the control groups [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, higher IMA levels were found in COVID-19 patients compared to control groups [ 24 , 25 , 26 ]. In Yucel et al’s study with 70 patients in the ICU, the serum IMA levels were determined to be significantly higher compared to the healthy control group [ 27 ]. However, in the study of Altıntas et al, no significant difference was determined in the serum IMA levels between the COVID-19 and the control groups [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies in the literature comparing the presence of additional disease and serum IMA levels in COVID-19 patients. In Yucel et al’s study, it was found that the levels of IMA were higher in COVID-19 patients with at least one chronic disease than in those without any such diseases [ 27 ]. In the study of Ogihara et al, in which they looked at the impact of obesity on disease severity in patients with COVID-19, a higher prevalence of HT and DM was found in the obesity group compared to the non-obese [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…They observed that higher levels of IMA, a marker of oxidative damage, were associated with the severity of pulmonary involvement, and suggested that IMA may be a predictive factor of pulmonary involvement. Yucel et al [21] determined that IMA levels in COVID-19 patients in the intensive care unit were relatively higher compared to healthy controls. They also observed that IMA levels in COVID-19 patients with chronic disease were significantly higher compared to those without and stated that the presence of chronic disease may lead to an increase in IMA levels by aggravating oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy people, free oxygen radicals produced by metabolism are removed by the antioxidant system, the body's defence mechanism. However, in COVID-19 patients, this radical damage is increased due to hypoxia, ischaemia, comorbidities, medical treatment and viral load [4][5][6] . Due to the widespread damage to cells and tissues caused by COVID-19 infection, it is difficult to identify of a specific laboratory parameter that can assess the severity of the disease and its impact on mortality.…”
Section: Introductionmentioning
confidence: 99%